Menurunkan Frequency Kecelakaan Subkontraktor dan Meningkatkan Kepuasan Pelanggan Melalui Penguatan Pilar Safety Governance di PT Putra Perkasa Abadi Jobsite Bib - Muhammad Osaegi Restu Amrulloh; Berthoni Gantino (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study aims to improve subcontractor safety performance through strengthening governance systems, leading safety indicators, capability building, and performance monitoring at PT Putra Perkasa Abadi (PPA) Jobsite Borneo Indobara (BIB). The research was motivated by the increasing trend of subcontractor incidents during Quarter 1 to Quarter 3 of 2025, where seven incidents occurred and exceeded the company threshold. In addition, subcontractor performance evaluation scores remained below the target threshold of 70, while customer satisfaction scores in subcontractor management decreased from 8.45 to 7.58. The study applied a continuous improvement approach using Quality Control Circle (QCC), Pareto analysis, Nominal Group Technique (NGT), and root cause analysis with the Ishikawa method. Improvement initiatives were implemented through four strategic pillars: strengthening governance, reinforcing leading indicators, capability building, and integrated dashboard monitoring. The implementation results showed significant improvements in subcontractor safety management. The subcontractor incident frequency rate was reduced to zero incidents in Quarter 4 of 2025, subcontractor performance evaluation increased above the threshold to 70.81, and customer satisfaction scores improved to 8.55. The findings indicate that structured governance strengthening combined with real-time monitoring and subcontractor engagement can significantly improve mining safety performance and stakeholder trust.